Future Traditions : Project Book. - Harmati, Hedvig; Vargha, Balázs (S.l. : MOME, 2018)
Papp, Zsófi ; Opedal Nordby, Hilde ; Horák, Enikö ; Pikush, Ivanna ; Vándor, Krisztina ; Tovseth Skomdal, Dina ; Veszprémi, Lili ; Myronenko, Oleksandra ; Wilhelmsen Sundin, Emelie ; Snikhovska, Kseniia ; Brilliantova, Marianna ; Bíró, Zsófi ; Bonin, Juliana Alexandra ; Zalavári, Fruzsina ; Dalen, Kristin ; Rea Kövér, Dóra ; Røkenes Christensen, Stian ; Szalai, Bálint ; Røhnebæk Stikbakke, Audun ; Wágner, Ákos ; Lévai, Levente
boek